Pilot-scale outdoor trial of a cyanobacterial consortium at pH 11 in a photobioreactor at high latitude. (June 2022) - Haines, Marianne; Vadlamani, Agasteswar; Daniel Loty Richardson, William; Strous, Marc
Graphical abstract: Highlights: A cyanobacterial consortium grew at high pH and high carbonate concentrations. Bicarbonate uptake pushed the pH > 11, sufficient for CO2 delivery by air capture. Biomass grew robustly in temperate outdoor conditions for 130 days. Productivity was between 3.1 and 5.8 g ash-free dry weight per square meter per day. Abstract: The biomass of microalgae and cyanobacteria yields a variety of products. Outdoor pilot plant trials typically grow a single species at circumneutral pH and provide CO2 by gas sparging. Here a cyanobacterial consortium was grown at high pH (beyond 11) and high dissolved carbonate concentrations (0.5 M) in an outdoor 1, 150 L tubular photobioreactor for 130 days in Calgary, Canada. The aim was to assess the productivity and robustness of the consortium. Importantly, the system was designed to enable future integration of air capture of CO2 . Productivity was between 3.1 and 5.8 g ash-free dry weight per square metre per day, depending on biomass density and month. 16S rRNA amplicon sequencing showed that cyanobacterium Candidatus "Phormidium alkaliphilum" made up 80% of the consortium. The consortium displayed robust growth and adapted to environmental conditions. Bicarbonate uptake pushed medium pH past 11, demonstrating the ability to achieve CO2 delivery by air capture.